Processing Of Galena From Air Piau, Kelantan - Zailani, Muhammad Dzafir Mohd (Universiti Sains Malaysia, 2017)
In this research work, a bulk sample of galena bearing ore for characterization and processing was obtained from Air Piau, Kelantan. The research work has been divided into two parts of method, characterization and processing. Characterization was performed for raw sample, after comminution and after processed. Characterization method used were XRF analyses to obtain chemical composition in the representative samples before processing and after being processed. Microscopy study using Kunah Robo Microscope and SEM/EDX are to identify and observe the liberation characteristic of galena minerals in the sample. Particle size distribution analyses were perform to determine the size and mineralogy of raw sample after undergo various stage of analyses process. For the processing, galena sample was undergo comminution process to liberate the minerals before it can be process using Froth Flotation method. From the characterization of raw sample, the grade of galena was low due to rate of liberation and interlocking of galena mineral with sphalerite, pyrite and quartz minerals. The grade of galena need to be optimized so that it can be economically processed in the industrial. To overcome the problem, comminution process using cone crusher and ring mill was choose to liberate the minerals before being concentrated by froth flotation. Data taken from different parameters that have been used for froth flotation were compared and it is shown that collector dosage 250 g/ton with conditioning time of 6 minutes and below 106 μm size fraction having the highest recovery rate of 98.94 %.